A possible role of the locus coeruleus in complex regional pain syndrome - Drummond, Peter D. (Frontiers in Integrative Neuroscience, 2012)
Heightened sensitivity to painful stimulation commonly spreads from the affected limb to the ipsilateral forehead in patients with complex regional pain syndrome (CRPS). In addition, acoustic startle evokes greater auditory discomfort and increases in limb pain when presented on the affected than unaffected side. In contrast, limb pain ordinarily evokes analgesia in the ipsilateral forehead of healthy participants, and acoustic startle suppresses limb pain. Together, these findings suggest that hemilateral and generalized pain control mechanisms are disrupted in CRPS, and that multisensory integrative processes are compromised. Failure to inhibit nociceptive input from the CRPS-affected limb could sensitize spinal and supraspinal neurons that receive convergent nociceptive and auditory information from hemilateral body sites. Somatosensory, auditory and emotional inputs may then aggravate pain by feeding into this sensitized nociceptive network. In particular, a disturbance in hemilateral pain processing that involves the locus coeruleus could exacerbate the symptoms of CRPS in some patients.